PENGARUH DISIPLIN KERJA TERHADAP PRESTASI KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN ASURANSI - Noersanti, Lina (SINERGI : Jurnal Riset Ilmiah, 2025)
The Process of developing a multilingual (Indonesian, Arabic, and English) three-dimensional (3D) animated learning media to introduce the body parts to early childhood at RA Baitus Syakur ( Kinder Garten ). The Media development was motivated by the lack of innovation in conventional two-dimensional learning media, which has resulted in the inability to optimally foster children's motivation and attention to learning. This study used a Research and Development (R&D) method with a simplified Borg and Gall model, encompassing the stages of needs analysis, product design, media creation, expert validation, revision, and limited and field trials. The field trial with 32 students showed significant improvements in body part recognition (20%), Indonesian vocabulary mastery (15%), and Arabic and English mastery (25%). Teacher and student responses also indicated a high level of satisfaction and enthusiasm for the developed media. This trilingual 3D animated learning media has proven feasible and effective in increasing learning of motivation, language skills and The understanding of human body concept interactively and enjoyable way for early childhood